Black Carbon at the Arctic Council. Mapping discourses and courses of action. - Pommereau Guitard, Galadrielle, 1998- (2021)
Black carbon emissions have a variety of adverse impacts both on humans, creating health problems and affecting crops, and on the environment and climate, as it is today the second contributor to climate change behind carbon dioxide. In spite of these important effects, emissions have rarely been addressed at international level so far. An exception to this is the Arctic Council, a high political regional forum which has taken upon itself to produce extensive scientific and technical knowledge as well as policy guiding on the matter for the past fifteen years. How did black carbon mitigation stay a priority for the Arctic Council? This study analyses the discourses surrounding the Council's black carbon policy and its many evolutions, looking for the different framing strategies used and their influence. Four main framings were identified : black carbon as a: (a) climate change issue; (b) health issue; (c) a pollution issue, and (d) a new scientific and political frontier for the Arctic Council to explore. All four framings have been used consistently throughout years but there is great variety in who uses them and why. The climate change framing appear as the more potent one until the global consensus around climate action crumbles after 2017. The sustained black carbon work of the Arctic Council shows, however, that consensus for action is not consensus on understanding, and that it is actually the different coexisting meanings that black carbon mitigation carries which allowed for sustained momentum and innovative policy making. Útblástur svarts kolefnis hefur margþætt neikvæð áhrif annarvegar á manneskjur, og hinsegar á umhverfið og loftslagið, þar sem útblástur svarts kolefnis er annar helsti áhrifaþáttur loftlagsbreytinga á eftir koltvísýringi. Þrátt fyrir þessi miklu áhrif, hefur útblásturinn lítið verið fjallaður um á alþjóðavettvangi. Ein af fáum undantekningu á þessu er Norðurskautsráðið, sem er pólitískur samstarfsvettvangur landa á norðurslóðum. Ráðið hefur tekið það að sér að rannsaka víðtæk ...